Non-Extensive Entropy Econometrics for Low Frequency Series National Accounts-Based Inverse Problems - Bwanakare, Second (De Gruyter, 2019)
The second edition of Non-extensive Entropy Econometrics for Low Frequency Series provides a new and robust power-law-based, non-extensive entropy econometrics approach to the economic modelling of ill-behaved inverse problems. Particular attention is paid to national account-based general equilibrium models known for their relative complexity. This new proposed approach could extend the frontier of theoretical and applied econometrics.